(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
Vitamin B12 blood level in patients with myeloma (C90 - International Classification of Diseases (ICD-10)), lymphocytic leukemia (C91) and myeloblastic leukemia (C92) prior and after the diagnosis and also BCR-ABL (fusion gene from breakpoint cluster region BCR gene and tyrosine-protein kinase ABL1 (Abelson murine leukemia) gene) tests for C92 patients were studied.Clinical records of 20 C92 patients in Riga East University Hospital were complemented with 6987 B12 clinical test data accumulated in E Gulbis laboratory (EGL) for 7451 patients over 20 years period. BCR-ABL and B12 dynamics for 11 patients with sufficient number of BCRABL and B12 tests were studied.Oracle Cloud with pseudonymized data replica from more than 350 000 000 original EGL clinical test data was used. The data were selected by online analytical processing and SQL built in tools and then used in offline analysis and visualization.Annually there are 107, 189 and 91 confirmed cases of C90, C91 and C92 in Latvia. EGL has 30% more C90-92 patients, due to suspected but later unconfirmed cases. Out of 7451 patients 1386 had one B12 test, two- 548, three and more- 864. The patients with diagnosis fluctuating between C90, C91 and C92 were excluded from the study. The data for the time period of 10 years before and after the first diagnosis were analyzed.Results. Methods and tools for data extraction and analysis from large amount of archived clinical test data were developed and applied. High and very high B12 level was observed for 53% of C92 patients starting from 3 years prior to diagnosis. For C90 and C91 patients B12 level changes around the diagnosis date were also observed although the effect was considerably smaller. Analysis of 11 selected patient data with clinical records showed timewise correlation between B12 and BCR-ABL for 3 of the patients.